Arman Begoyan’s cognitive-conceptual therapy: an overview and some techniques - Arakelyan, Tatevik; Begoyan, Arman (Scripta Neophilologica Posnaniensia, 2018)
Arman Begoyan’s cognitive-conceptual therapy: an overview and some techniques